Al-'Arābīyah and Basa Sunda: Ideologies of Translation and Interpretation among the Muslim of West Java - Zimmer, Benjamin G. (Studia Islamika, 2000)
This article reflects on these questions as they relate to the Sundanese-speaking population of western Java, Indonesia's second largest ethnic group. "Sundaneseness" is to a great extent defined by vernacular usage of the local language, basa Sunda, which is related to but distinct from Javanese, Indonesian, and the other Austronesian languages of the region. Speakers of Sundanese currently number more than 30 million, rivaling the populations of such countries as Canada, Morocco, and Kenya (and twice the population of their erstwhile colonizers, the Netherlands), yet Western scholarly literature on "Java" has paid them scant attention. Ethnographic studies of the island's Muslim communities, from Geertz's Religion of Java to Woodward's Islam in Java, have been similarly skewed towards the dominant Javanese ethno linguistic group inhabiting central and eastern Java.DOI: 10.15408/sdi.v7i3.702